MENINGKATKAN PRESTASI HASIL BELAJAR MATEMATIKA MATERI KELILING DAN LUAS BANGUN DATAR MELAUI ALAT PERAGA BANGUN DATAR PADA SISWA KELAS IV SDN 01 SURUH KECAMATAN TASIKMADU KABUPATEN KARANGNYAR SEMESTER I TAHUN PELAJARAN 2014/2015 - Rahayu, Indriyati (UNIVERSITAS SLAMET RIYADI, 2015)
The problem of this research is the effort to improve the mathematics achievement aboutperimeter and area of plane through plane visual aids to the fourth grade students in SDN 01Suruh Tasikmadu Karanganyar at semester 1 in the academic year of 2014/2015.The purpose of this research is to improve the mathematics achievement about perimeterand area of plane to the fourth grade students in SDN 01 Suruh Tasikmadu Karanganyar atsemester 1 in the academic year of 204/2015 through plane visul aids in the learning process.The kind of this research is Classroom Action Research that consists of four stages. Theyare planning, carrying out the action, observation, and reflection. Those stages then build acycle. This research includes three cycles. The technique of data collecting is interactive analysismodel. It is the relationship among three components, they are: data reduction, data verification,and conclusion.The result of this research is it is can be drawn a conclusion that the use of plane visualaids can improve the mathematics achievements about perimeter and area of plane to the fourthstudents in SDN 01 Suruh Tasikmadu Karangnayar at semester 1 in the academic year of2014/2015. It can be seen from the average score in pre research is 62, while in cycle 1 is 70 and78 in cycle 2. Therefore, the use of plane visual aids can significantly improve the mathematicsachievement about perimeter and area of plane to the fourth grade students in SDN 01 SuruhTasikmadu Karanganyar at semester 1 in the academic year of 2014/2015.Key words: Plane visual aids, achievement, Mathematics.